Judges chronopies and judges famas - Coaguila Valdivia, Jaime Francisco (2008)
The book History of cronopios and famas by Julio Cortazar was written to fight against the pragmatism, the pre made and the solemnity, characteristics than more than once identified  the Judicial Power. Making a metaphorical analysis applied to the law, the flaws, prejudices and rigor of the role of magistrates are exposed, making a contrast of the so-called cronopios judges and fama judges within a judicial panorama.